2016
DOI: 10.1016/j.rse.2016.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Integrating chlorophyll fAPAR and nadir photochemical reflectance index from EO-1/Hyperion to predict cornfield daily gross primary production

Abstract: strongly affects seasonal chl and PRInadir. We demonstrate the potential capacity to monitor GPP with space-based visible through shortwave infrared (VSWIR) imaging spectrometers such as NASA's soon to be decommissioned EO-1/Hyperion and the future Hyperspectral Infrared Imager (HyspIRI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 101 publications
0
15
0
1
Order By: Relevance
“…In this study we have addressed the change in SIF properties from juvenile to mature stands, however future research, considering the natural lifespan of the loblolly trees of 100+ years of age (Burns & Honkala, ), is needed to confirm our findings. Moreover, accurate determination of true SIF yield should require an estimation of PAR absorbed by green leaves (e.g., Gitelson & Gamon, ; Zhang et al., ) and this could be another key point that should be considered for future investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we have addressed the change in SIF properties from juvenile to mature stands, however future research, considering the natural lifespan of the loblolly trees of 100+ years of age (Burns & Honkala, ), is needed to confirm our findings. Moreover, accurate determination of true SIF yield should require an estimation of PAR absorbed by green leaves (e.g., Gitelson & Gamon, ; Zhang et al., ) and this could be another key point that should be considered for future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, accurate determination of true SIF yield should require an estimation of PAR absorbed by green leaves (e.g., Gitelson & Gamon, 2015;Zhang et al, 2016) and this could be another key point that should be considered for future investigations.…”
Section: Sun-induced Canopy Fluorescence and Agerelated Processesmentioning
confidence: 99%
“…The pixel size of TOROPOMI is 7 km by 7 km. For satellite monitoring of PRI, one of the possible options is using EO‐1's Hyperion (Asner, Nepstad, Cardinot, & Ray, ; Zhang et al, ). Hyperion can measure at a relatively high spatial resolution (30 m) for user‐selected sites, but it was deactivated on March 2017.…”
Section: Discussionmentioning
confidence: 99%
“…APARchl is considered to be the first 30 order approximation of SIF as it exhibits high correlation with SIF at the canopy scale (Du et al, 2017;Rossini et al, 2016;Verrelst et al, 2015;Zhang et al, 2018c). Previous studies have shown that fPARchl can be inversely estimated using the surface reflectances and radiative transfer models (Zhang et al, 2005(Zhang et al, , 2016a. The canopy structure information that affects the SIF reabsorption within canopy is also embedded in the near infrared reflectance (Badgley et al, 2017;Knyazikhin et al, Biogeosciences Discuss., https://doi.org /10.5194/bg-2018-255 Manuscript under review for journal Biogeosciences Discussion started: 22 June 2018 c Author(s) 2018.…”
Section: Introductionmentioning
confidence: 99%